2015
DOI: 10.1039/c5nr00420a
|View full text |Cite
|
Sign up to set email alerts
|

Efficient inorganic solid solar cells composed of perovskite and PbS quantum dots

Abstract: Lead halide perovskite solar cells have attracted great interest due to their high efficiency and simple fabrication process. However, the high efficiency heavily relies on expensive organic hole-transporting materials (OHTMs) such as 2,2',7,7'-tetrakis(N,N-di-p-methoxyphenylamine)-9,9'-spirobifluorene (spiro-MeOTAD), it is preferable to replace these expensive OHTMs by inorganic and low cost materials. Here, we report colloidal PbS quantum dots synthesized by a facile method and used as the inorganic hole-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…Such systems have recently emerged as a new research hotspot, the attention focused mainly on combinations of PbS or PbSe NCs with Pb-based perovskites. In particular, PbS NCs introduced into MAPI-based solar cells were found to act simultaneously as a co-absorber and an HTL, rendering the use of additional organic hole transporting materials superfluous [211212]. A shell of MAPI on the surface of PbS NCs was found to act as an efficient electron acceptor and a passivating agent, minimizing the recombinational losses in lead sulfide NCs [213214].…”
Section: Reviewmentioning
confidence: 99%
“…Such systems have recently emerged as a new research hotspot, the attention focused mainly on combinations of PbS or PbSe NCs with Pb-based perovskites. In particular, PbS NCs introduced into MAPI-based solar cells were found to act simultaneously as a co-absorber and an HTL, rendering the use of additional organic hole transporting materials superfluous [211212]. A shell of MAPI on the surface of PbS NCs was found to act as an efficient electron acceptor and a passivating agent, minimizing the recombinational losses in lead sulfide NCs [213214].…”
Section: Reviewmentioning
confidence: 99%
“…The bilayer structure increases the complexity of the device structure but also need to prevents impairment of the perovskite layer during film processing of the PbS QD layer. Additionally, many studies have focused on utilizing the excellent hole‐transporting capability of PbS QDs as the p‐type hole‐transporting layer for perovskites, but this technique does not utilize the NIR absorption ability of PbS QDs to extend the spectral response range …”
Section: Introductionmentioning
confidence: 99%
“…These excellent studies have realized the hybridization of PbS QDs and perovskite, but the application of hybrid perovskite:PbS QD structures in Vis–NIR PePDs is still obstructed by several challenging issues: (i) The mechanism of charge carrier transfer between the doped PbS QDs and the perovskite has not been revealed. (ii) In these reports, small‐diameter PbS QDs, which can only improve visible‐region absorption, were doped into perovskite . Therefore, this problematic issue must be solved by using large‐diameter PbS QDs to expand NIR absorption.…”
Section: Introductionmentioning
confidence: 99%
“…J‐V curves revealed that PCE of PSCs can be tuned by modifying the sizes of PbS QDs via energy levels of PbS QD alignment with the perovskite (Figure c). Subsequently, Dai and co‐workers also developed the hybrid PSCs using colloidal PbS QDs as inorganic HTM and showed the efficiency nearly 8 % with good stability . In this report, the devices were fabricated by optimizing the thickness of PbS QDs using two‐step coating method and achieved a PCE of 7.8 %, whereas one‐step method gave 4.73 %.…”
Section: Inorganic Htm Based Pscsmentioning
confidence: 89%